The Role of Biomechanics in Liver Tissue Engineering - Moran, Emma (Wake Forest University, 2015)
The field of liver bioengineering aims to generate functioning liver tissue in the laboratory in order to study complicated processes such as development, disease, cancer, drug metabolism, or even to engineer organs that can be implanted in patients. One approach in liver tissue engineering is to use the process of decellularization to create acellular liver scaffolds that retain the native tissue's extracellular matrix and architecture. These scaffolds can then be repopulated with a variety of hepatic and non-hepatic cell-types depending on the application, or in the case of human transplantation, the patient's own cells. While there has been some success in transplanting these constructs in animals and applying them towards simplistic models, we are still far away from achieving physiological liver structure and function. In order to achieve this, seeded cells need to be placed within the proper environment and given particular biological cues in order to function as they would physiologically. One important aspect of this process is the mechanical environment and signaling that cells experience within the acellular liver scaffolds. This thesis aims to investigate the role of biomechanics in liver tissue engineering so that we can better understand how to deliver the proper mechanical stimuli to cells in order to optimize their growth and function. To this end, we first characterized changes in liver biomechanics with tissue decellularization, finding that this process increases scaffold permeability and lowers matrix stiffness. Next, we investigated the impact of fluid flow-driven forces on cell seeding, tissue growth and cellular organization in a bioengineered liver with capabilities of modeling liver development and disease. Finally, we developed a bioengineered liver model of colon cancer metastasis in which we analyzed the influence of fluid flow and matrix stiffness on tumor behavior. Overall, the findings of this thesis demonstrate the importance of the biomechanical environment in creating successful bioengineered liver models.
Keywords: Liver; Regenerative Medicine; Soft tissue mechanics; Tissue Engineering; Whole organ decellularization